Aktan dalam Novel The Maze Runner Karya James Dashner: Kajian Naratologi A. J. Greimas (Actants in James Dashner's The Maze Runner Novel: A Study of Narrative A. J. Greimas) - Ayu Misriyani; Endry Boeriswati; Herlina Herlina (Jurusan Tadris Bahasa Indonesia, 2022)
This study aims to describe the actant in The Maze Runner novel based on the scheme of the actant, and the structure of the story. Methods of data collection is done by reading notes technique. This study uses content analysis because it prioritizes the depth of appreciation of the interactions between concepts that are being studied empirically. The results of the research show that there are three acts which are divided into three chapters in this novel. The actant and functional structures in The Maze Runner novel are complex and have fulfilled all stages. This novel can be used as literature learning material, especially novels.Penelitian ini bertujuan untuk mendeskripsikan aktan dalam novel The Maze Runner berdasarkan skema aktannya, dan struktur cerita. Metode pengumpulan data dilakukan dengan teknik baca catat. Penelitian ini menggunakan analisis isi karena mengutamakan kedalaman penghayatan interaksi antar-konsep yang sedang dikaji secara empiris. Hasil penelitian menunjukkan bahwa terdapat tiga aktan yang terbagi dalam tiga bab di novel ini. Struktur aktan dan fungsional dalam novel The Maze Runner sudah kompleks dan sudah memenuhi semua tahapan. Novel ini dapat digunakan sebagai materi pembelajaran sastra, khususnya novel.